Neonatal Polycythemia: Prevalence, Risk Factors and Predictors of Severity - Alice da Silva Martins (2020)
Background: Polycythemia is a hematological condition with several causes and risk factors. The clinical presentation is variable, ranging from asymptomatic newborns to cases with severe physiological changes that can be fatal. The aim of this study was to assess the prevalence, risk factors and predictors of severity of polycythemia in a Portuguese level III Neonatal Intensive Care Unit (NICU). Methods: Retrospective study of all term newborns admitted to the NICU of "Centro Hospitalar e Universitário de São João" between 1999 and 2019 and meeting one of the following inclusion criteria were eligible for the study: 1) Hematocrit > 65% or Hemoglobin > 22 g/dl; 2) Hemoglobin ≥ 21 g/dl with clinical manifestations of polycythemia. Results: Of the 78 newborns diagnosed with polycythemia, a total of 53 fulfilled the inclusion criteria and were included in the study, corresponding to a prevalence of 0.57%. Birth outside the hospital was the only risk factor with statistical significance. Of 53 cases, 51 (96.23%) had symptomatic polycythemia. The most frequent symptoms were: hyperbilirubinemia (69.81%), hypoglycemia (52.83%), thrombocytopenia (50.94%), cardiorespiratory (33.96%) and neurological symptoms (33.96%). Of the 53 newborns evaluated, 41 (77.36%) needed treatment. The only risk factors that influenced the hematocrit value were maternal diabetes and fetal growth restriction. Conclusions: The best way to improve the prognosis of polycythemia is to identify the risk factors present throughout pregnancy and make an early diagnosis and treatment. Out-of-hospital births should be avoided. The diagnosis shouldn't be excluded, even if hemoglobin and hematocrit are within normal limits.